Genetics and genomic medicine in Mali: challenges and future perspectives. Issue 2 (March 2016) - Landouré, Guida; Samassékou, Oumar; Traoré, Mahamadou; Meilleur, Katherine G.; Guinto, Cheick Oumar; Burnett, Barrington G.; Sumner, Charlotte J.; Fischbeck, Kenneth H.
Abstract : Genetics and genomic medicine in Mali: challenges and future perspectives.